Micro-nano structure carbon fiber paper for gas diffusion layer and preparation method and application of micro-nano structure carbon fiber paper
The preparation of micro-nano structure carbon fiber paper through high-voltage electrospinning and wet papermaking technology has solved the problem of insufficient mechanical strength of carbon fiber paper, improved the permeability and conductivity of the gas diffusion layer of the fuel cell, and achieved more efficient electrochemical performance.
Patent Information
- Application Number
- CN202310654927.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-05
AI Technical Summary
The existing domestic carbon fiber paper has insufficient mechanical strength and cannot meet the permeability, breathability and conductivity requirements of the gas diffusion layer of fuel cell.
Boron-containing polyacrylonitrile nanofibers are prepared by high-pressure electrospinning. After pre-oxidation treatment and wet papermaking, combined with chopped carbon fiber, binder and dispersant, micro-nano structure carbon fiber paper is prepared by impregnation resin and hot pressing curing to form A gas diffusion layer with a micro-nano gradient pore structure.
The mechanical strength, permeability and conductivity of the gas diffusion layer are significantly improved, the resistivity is reduced, the electrochemical performance of the fuel cell is improved, and the energy consumption cost is saved.
Smart Images

Figure CN119121692A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a micro-nano structure carbon fiber paper for a gas diffusion layer, a preparation method and an application thereof. The micro-nano structure carbon fiber paper for a gas diffusion layer is mainly used for a gas diffusion layer of a fuel cell. Background Art
[0002] In the context of low-carbon development and energy transformation, the hydrogen energy industry has achieved a good development trend in my country. Hydrogen energy is an important carrier for building a diversified energy structure dominated by renewable energy in the future, and its development and utilization technology has also become an important direction for a new round of world energy technology changes. Among them, hydrogen fuel cells are power generation devices that directly convert the chemical energy of hydrogen and oxygen into electrical energy. They can realize the mobility, lightweight and large-scale popularization of hydrogen energy, and can be widely used in transportation, industry, construction, military and other fields.
[0003] The membrane electrode is the place where the electrochemical reaction of hydrogen fuel cells occurs. As one of the core components of the membrane electrode, the gas diffusion layer mainly provides a transmission channel for the gases involved in the reaction and the generated water, and supports the catalyst. Its performance has a direct impact on the performance of the fuel cell. The development of high-performance, low-cost, and domestically produced gas diffusion layers is one of the key factors in accelerating the implementation of the fuel cell industry.
[0004] At present, the domestic carbon fiber paper manufacturing technology cannot meet the needs of fuel cell gas diffusion layers. Chinese Patent Application No. CN201911066598.3 mixes porous carbon materials into mesophase asphalt, stirs and swells them, and obtains mesophase asphalt modified with porous carbon materials. The primary fiber membrane is prepared by melt spinning or electrostatic spinning, and carbon paper is prepared after pre-oxidation, carbonization and graphitization. Chinese Patent Application No. CN202110774730.7 discloses a process for preparing thin carbon paper, which uses polyacrylonitrile or asphalt as raw materials and functionalized ionic liquid as a dopant. The carbon paper substrate is spun by electrostatic spinning technology, and then the resin solution after solvent treatment is impregnated, hot-pressed and cured, pre-oxidized, carbonized, and graphitized to prepare thin carbon paper. However, the carbon paper prepared by the above method has insufficient mechanical strength, and the transmission performance of gas and water still needs to be further optimized. Summary of the invention
[0005] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a micro-nanostructured carbon fiber paper for a gas diffusion layer, a preparation method and an application thereof, which can solve the problem of insufficient mechanical strength of carbon paper in the prior art, and at the same time improve the permeability, air permeability and electrical conductivity of the gas diffusion layer of the fuel cell; the micro-nanostructured carbon fiber paper prepared by the present invention has a micro-nano composite structure, and the gas diffusion layer has a lower resistivity and a higher air permeability, which can effectively improve the electrochemical performance of the fuel cell.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer, comprising the following steps:
[0008] S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning;
[0009] S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples;
[0010] S3, mixing the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, a binder, a dispersant and water uniformly and then performing wet papermaking to obtain a micro-nanostructured carbon fiber base paper;
[0011] S4, the micro-nano structure carbon fiber base paper is impregnated with resin, hot-pressed and cured, and heat-treated to obtain micro-nano structure carbon fiber paper for gas diffusion layer.
[0012] Preferably, in step S1:
[0013] The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.1-20):(500-3000); and / or
[0014] The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; and / or
[0015] The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or
[0016] The stirring temperature is 30 to 90° C.; and / or
[0017] The high-voltage electrospinning is one of single-needle, multi-needle and needle-free.
[0018] Preferably, in step S1:
[0019] The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.5-10):(800-2000); and / or
[0020] The stirring temperature is 40-80°C.
[0021] Preferably, in step S2:
[0022] The pre-oxidation treatment is carried out in an air atmosphere at 180-300° C. for a treatment time of 0.5-5 h; and / or
[0023] The boron-containing pre-oxidized nanofiber short filaments have a length of 0.5 to 12 cm and a diameter of 50 to 800 nm.
[0024] Preferably, in step S2:
[0025] In the pre-oxidation treatment, the treatment temperature is 200-280° C. and the treatment time is 1-4 hours; and / or
[0026] The boron-containing pre-oxidized nanofiber short filaments have a length of 2 to 8 cm and a diameter of 100 to 600 nm.
[0027] Preferably, in step S3:
[0028] The weight ratio of the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (0.1-5):(0.1-5):(0.1-4):(0.05-2):100; and / or
[0029] The chopped carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber and viscose-based carbon fiber; and / or
[0030] The binder is selected from one or more of polyvinyl alcohol, epoxy resin and carboxymethyl cellulose; and / or
[0031] The dispersant is selected from one of polyethylene oxide, polyacrylamide and sodium polyacrylate; and / or
[0032] The thickness of the micro-nano structure carbon fiber base paper is 200-800 μm.
[0033] Preferably, in step S3:
[0034] The weight ratio of the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (0.2-3):(0.2-3):(0.2-2.5):(0.1-1.5):100; and / or
[0035] The thickness of the micro-nano structure carbon fiber base paper is 300-600 μm.
[0036] Preferably, in step S4:
[0037] The resin used for the impregnation resin is selected from one or more of phenolic resin, epoxy resin and furan resin; and / or
[0038] During the hot pressing curing process, the hot pressing temperature is 80-300° C., the pressure is 0.5-20 MPa, and the hot pressing time is 1-30 min; and / or
[0039] The heat treatment process is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or
[0040] The thickness of the micro-nano structure carbon fiber paper for the gas diffusion layer is 100-400 μm.
[0041] Preferably, in step S4:
[0042] During the hot pressing curing process, the hot pressing temperature is 100-240° C., the pressure is 1-10 MPa, and the hot pressing time is 2-15 min; and / or
[0043] During the heat treatment, the heat treatment temperature is 800-2000° C. and the heat treatment time is 1-3 hours; and / or
[0044] The thickness of the micro-nano structure carbon fiber paper for the gas diffusion layer is 140-280 μm.
[0045] The second aspect of the present invention provides a micro-nano structured carbon fiber paper for a gas diffusion layer prepared according to the method for preparing the micro-nano structured carbon fiber paper for a gas diffusion layer according to the first aspect of the present invention.
[0046] Preferably, the vertical air permeability of the micro-nanostructured carbon fiber paper used for the gas diffusion layer is ≥2200 mL·mm / (cm 2 ·h·mmAq), vertical resistivity ≤55mΩ·cm, parallel resistivity ≤4.0mΩ·cm, tensile strength ≥50MPa, bending modulus ≥12GPa.
[0047] The third aspect of the present invention provides an application of the micro-nanostructured carbon fiber paper for gas diffusion layer prepared by the method for preparing the micro-nanostructured carbon fiber paper for gas diffusion layer described in the first aspect of the present invention in the gas diffusion layer of a liquid flow battery.
[0048] The micro-nanostructured carbon fiber paper for gas diffusion layer provided by the present invention, as well as the preparation method and application thereof, has the following characteristics:
[0049] Beneficial effects:
[0050] 1. The micro-nano structured carbon fiber paper prepared by the present invention has both nano-scale carbon fibers and micron-scale carbon fibers, forming a micro-nano gradient pore structure, which effectively improves the permeability, air permeability and electrical conductivity of the gas diffusion layer while having a certain mechanical strength;
[0051] 2. The present invention adds nano-boride to the spinning solution to evenly disperse the boron element in the boron-containing polyacrylonitrile fiber, thereby improving the catalytic graphitization effect of boron, reducing the graphitization temperature, and increasing the degree of graphitization, so that the carbonization and graphitization of the boron-containing pre-oxidized nanofiber short filaments can be completed at a relatively low heat treatment temperature of the carbon fiber base paper, thereby greatly saving energy consumption costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0053] Figure 1 The present invention is a schematic flow chart of a method for preparing micro-nanostructured carbon fiber paper for a gas diffusion layer. DETAILED DESCRIPTION
[0054] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0055] Combination Figure 1 As shown, a method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of the present invention comprises the following steps:
[0056] S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning;
[0057] Specifically, polyacrylonitrile powder, nano-boride and organic solvent are prepared in a weight ratio of 100:(0.1-20):(500-3000), polyacrylonitrile powder and nano-boride are added to the organic solvent, stirred at 30-90°C until uniformly dissolved, to form a spinning solution, and boron-containing polyacrylonitrile nanofibers are prepared by high-voltage electrospinning. In a specific embodiment, the weight ratio of polyacrylonitrile powder, nano-boride and organic solvent is 100:(0.5-10):(800-2000); in a further preferred embodiment, the weight ratio of polyacrylonitrile powder, nano-boride\organic solvent is 100:(2-5):(900-1600). The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; the organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; the stirring temperature is 40-80°C; and the high-voltage electrospinning is one of single needle, multi-needle and needleless.
[0058] S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples;
[0059] Specifically, the boron-containing polyacrylonitrile nanofiber obtained in step S1 is subjected to a pre-oxidation treatment in an air atmosphere at 180-300° C. for 0.5-5 hours, and then subjected to an opening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 3-12 cm and a diameter of 50-800 nm. In a specific embodiment, during the pre-oxidation treatment, the treatment temperature is 200-280° C., and the treatment time is 1-4 hours; the length of the obtained boron-containing pre-oxidized nanofiber short filaments is 5-9 cm, and the diameter is 100-600 nm.
[0060] S3, mixing the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, a binder, a dispersant and water uniformly and then performing wet papermaking to obtain a micro-nanostructured carbon fiber base paper;
[0061] Specifically, the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water obtained in step S2 are mixed evenly in a weight ratio of (0.1-5):(0.1-5):(0.1-4):(0.05-2):100, and then wet papermaking is performed to obtain a micro-nano structure carbon fiber base paper with a thickness of 200-800 μm. Among them, the chopped carbon fibers are selected from one or more of polyacrylonitrile-based carbon fibers, asphalt-based carbon fibers and viscose-based carbon fibers; the binder is selected from one or more of polyvinyl alcohol, epoxy resin and carboxymethyl cellulose; the dispersant is selected from one of polyethylene oxide, polyacrylamide and sodium polyacrylate. In a specific embodiment, the weight ratio of boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (0.2-3): (0.2-3): (0.2-2.5): (0.1-1.5): 100; in a further preferred embodiment, the weight ratio of boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (2-2.8): (1-2.8): (0.3-0.6): (0.2-0.3): 100. The thickness of the micro-nanostructured carbon fiber base paper is 300-600 μm.
[0062] S4, obtaining micro-nano structure carbon fiber paper for gas diffusion layer by impregnating the micro-nano structure carbon fiber base paper with resin, hot pressing and curing, and heat treating.
[0063] Specifically, the micro-nano structure carbon fiber base paper obtained in step S3 is impregnated with resin, hot-pressed and cured at 80-300° C. and 0.5-20 MPa for 1-30 min, and heat-treated at 600-2500° C. in a nitrogen atmosphere for 0.5-4 h to obtain a micro-nano structure carbon fiber paper for a gas diffusion layer with a thickness of 100-400 μm. The resin used for impregnation with the resin is selected from one or more of phenolic resin, epoxy resin, and furan resin. In a specific embodiment, during the hot pressing curing process, the hot pressing temperature is 100-240°C, the pressure is 1-10 MPa, and the hot pressing time is 2-15 min; during the heat treatment process, the heat treatment temperature is 800-2000°C, and the heat treatment time is 1-3 h; in a further preferred embodiment, during the hot pressing curing process, the hot pressing temperature is 130-190°C, the pressure is 1.5-5 MPa, and the hot pressing time is 4-10 min; during the heat treatment process, the heat treatment temperature is 1200-1700°C, and the heat treatment time is 1.5-2 h. The thickness of the micro-nanostructure carbon fiber paper for the gas diffusion layer is 140-280 μm.
[0064] The present invention also provides a micro-nano structured carbon fiber paper for a gas diffusion layer prepared according to the above-mentioned preparation method of the micro-nano structured carbon fiber paper for a gas diffusion layer. The vertical air permeability of the micro-nano structured carbon fiber paper for a gas diffusion layer is ≥2200mL·mm / (cm 2 ·h·mmAq), vertical resistivity ≤55mΩ·cm, parallel resistivity ≤4.0mΩ·cm, tensile strength ≥50MPa, bending modulus ≥12GPa.
[0065] The present invention also provides an application of the micro-nanostructured carbon fiber paper for gas diffusion layer in a fuel cell gas diffusion layer.
[0066] The micro-nanostructured carbon fiber paper for gas diffusion layer of the present invention, as well as its preparation method and application are further introduced below with reference to specific examples.
[0067] Example 1
[0068] The method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of this embodiment adopts the following steps:
[0069] (1) Weigh 10 g of polyacrylonitrile powder and 0.2 g of nano-boron carbide, add them to 100 g of dimethylformamide, stir at 50° C. until they are uniformly dissolved to form a spinning solution, and prepare boron-containing polyacrylonitrile nanofibers using a single-needle electrospinning device.
[0070] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 220° C. for 1.5 hours, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 3 mm and a diameter of 200 nm.
[0071] (3) Weigh 2 g of the boron-containing pre-oxidized nanofiber short filaments obtained in step (2), 2 g of polyacrylonitrile-based short carbon fibers, 0.5 g of polyvinyl alcohol, 0.2 g of polyethylene oxide, and 100 g of water, mix them evenly, and then perform wet papermaking to obtain a micro-nanostructured carbon fiber base paper with a thickness of 342 μm.
[0072] (4) The micro-nanostructured carbon fiber base paper obtained in step (3) is impregnated in phenolic resin, then hot-pressed and cured at 180° C. and 2 MPa for 5 min, and finally heat-treated at 1500° C. in a nitrogen atmosphere for 2 h to obtain a micro-nanostructured carbon fiber paper for a fuel cell gas diffusion layer with a thickness of 190 μm.
[0073] The vertical air permeability of the prepared micro-nanostructured carbon fiber paper is 2300 mL·mm / (cm 2 ·h·mmAq), perpendicular resistivity 50mΩ·cm, parallel resistivity 3.8mΩ·cm, perpendicular thermal conductivity 2.3W / (m·K), parallel thermal conductivity 25W / (m·K), tensile strength 55MPa, bending modulus 12GPa, which are significantly better than commercial carbon paper.
[0074] Example 2
[0075] The method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of this embodiment adopts the following steps:
[0076] (1) 10 g of polyacrylonitrile powder and 0.3 g of nano-boron nitride were weighed, added to 120 g of dimethylacetamide, and stirred at 60° C. until uniformly dissolved to form a spinning solution, and boron-containing polyacrylonitrile nanofibers were prepared by a multi-needle electrospinning device.
[0077] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 230° C. for 1 hour, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 4 mm and a diameter of 300 nm.
[0078] (3) Weigh 2 g of the boron-containing pre-oxidized nanofiber short filaments obtained in step (2), 1.5 g of polyacrylonitrile-based short carbon fibers, 0.5 g of asphalt-based short carbon fibers, 0.6 g of carboxymethyl cellulose, 0.3 g of polyacrylamide, and 100 g of water, mix them evenly, and then perform wet papermaking to obtain a micro-nanostructured carbon fiber base paper with a thickness of 390 μm.
[0079] (4) The micro-nanostructured carbon fiber base paper obtained in step (3) is impregnated in phenolic resin, then hot-pressed and cured at 150° C. and 3 MPa for 7 min, and finally heat-treated at 1300° C. in a nitrogen atmosphere for 1.5 h to obtain a micro-nanostructured carbon fiber paper for a fuel cell gas diffusion layer with a thickness of 228 μm.
[0080] The vertical air permeability of the prepared micro-nanostructured carbon fiber paper is 2250 mL·mm / (cm 2 ·h·mmAq), perpendicular resistivity 45mΩ·cm, parallel resistivity 3.2mΩ·cm, perpendicular thermal conductivity 2.4W / (m·K), parallel thermal conductivity 27W / (m·K), tensile strength 58MPa, flexural modulus 13GPa, which are significantly better than commercial carbon paper.
[0081] Example 3
[0082] The method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of this embodiment adopts the following steps:
[0083] (1) 10 g of polyacrylonitrile powder and 0.35 g of nano-zirconium boride were weighed, added to 150 g of dimethyl sulfoxide, and stirred at 55° C. until uniformly dissolved to form a spinning solution, and boron-containing polyacrylonitrile nanofibers were prepared by a needleless electrospinning device.
[0084] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 210° C. for 2 hours, and then subjected to an opening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 6 mm and a diameter of 400 nm.
[0085] (3) Weigh 2 g of the boron-containing pre-oxidized nanofiber short filaments obtained in step (2), 2.5 g of polyacrylonitrile-based short carbon fibers, 0.3 g of asphalt-based short carbon fibers, 0.5 g of epoxy resin, 0.25 g of sodium polyacrylate, and 100 g of water, mix them evenly, and then perform wet papermaking to obtain a micro-nanostructured carbon fiber base paper with a thickness of 510 μm.
[0086] (4) The micro-nanostructured carbon fiber base paper obtained in step (3) is impregnated in phenolic resin, then hot-pressed and cured at 130° C. and 5 MPa for 4 min, and finally heat-treated at 1700° C. in a nitrogen atmosphere for 1 h to obtain a micro-nanostructured carbon fiber paper for a fuel cell gas diffusion layer with a thickness of 256 μm.
[0087] The vertical air permeability of the prepared micro-nanostructured carbon fiber paper is 2350 mL·mm / (cm 2·h·mmAq), perpendicular resistivity 52mΩ·cm, parallel resistivity 3.9mΩ·cm, perpendicular thermal conductivity 2.1W / (m·K), parallel thermal conductivity 25W / (m·K), tensile strength 60MPa, bending modulus 12GPa, which are significantly better than commercial carbon paper.
[0088] Example 4
[0089] The method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of this embodiment adopts the following steps:
[0090] (1) 10 g of polyacrylonitrile powder and 0.2 g of nano-titanium boride were weighed, added to 160 g of dimethylformamide, and stirred at 60° C. until uniformly dissolved to form a spinning solution, and boron-containing polyacrylonitrile nanofibers were prepared by a needleless electrospinning device.
[0091] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 230° C. for 1.5 hours, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 6 mm and a diameter of 150 nm.
[0092] (3) Weigh 2 g of the boron-containing pre-oxidized nanofiber short filaments obtained in step (2), 1.5 g of polyacrylonitrile-based short carbon fibers, 0.2 g of viscose-based short carbon fibers, 0.3 g of polyvinyl alcohol, 0.3 g of sodium polyacrylate, and 100 g of water, mix them evenly, and then perform wet papermaking to obtain a micro-nanostructured carbon fiber base paper with a thickness of 485 μm.
[0093] (4) The micro-nanostructured carbon fiber base paper obtained in step (3) is impregnated in phenolic resin, then hot-pressed and cured at 190° C. and 1.5 MPa for 8 min, and finally heat-treated at 1200° C. in a nitrogen atmosphere for 2 h to obtain a micro-nanostructured carbon fiber paper for a fuel cell gas diffusion layer with a thickness of 268 μm.
[0094] The vertical air permeability of the prepared micro-nanostructured carbon fiber paper is 2300 mL·mm / (cm 2 ·h·mmAq), perpendicular resistivity 49mΩ·cm, parallel resistivity 3.6mΩ·cm, perpendicular thermal conductivity 2.2W / (m·K), parallel thermal conductivity 25W / (m·K), tensile strength 53MPa, bending modulus 13GPa, which are significantly better than commercial carbon paper.
[0095] Example 5
[0096] The method for preparing a micro-nanostructured carbon fiber paper for a gas diffusion layer of this embodiment adopts the following steps:
[0097] (1) 10 g of polyacrylonitrile powder and 0.5 g of nano-boron carbide were weighed, added to 90 g of dimethylformamide, and stirred at 60° C. until uniformly dissolved to form a spinning solution, and boron-containing polyacrylonitrile nanofibers were prepared by a single-needle electrospinning device.
[0098] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 215° C. for 2 hours, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 4 mm and a diameter of 450 nm.
[0099] (3) Weigh 2.8 g of the boron-containing pre-oxidized nanofiber short filaments obtained in step (2), 1 g of polyacrylonitrile-based short carbon fibers, 0.4 g of polyvinyl alcohol, 0.25 g of polyacrylamide, and 100 g of water, mix them evenly, and then perform wet papermaking to obtain a micro-nanostructured carbon fiber base paper with a thickness of 420 μm.
[0100] (4) The micro-nanostructured carbon fiber base paper obtained in step (3) is impregnated in phenolic resin, then hot-pressed and cured at 175°C and 2MPa for 10 min, and finally heat-treated at 1400°C in a nitrogen atmosphere for 2.5 h to obtain a micro-nanostructured carbon fiber paper for a fuel cell gas diffusion layer with a thickness of 213 μm.
[0101] The vertical air permeability of the prepared micro-nanostructured carbon fiber paper is 2500 mL·mm / (cm 2 ·h·mmAq), perpendicular resistivity 45mΩ·cm, parallel resistivity 3.2mΩ·cm, perpendicular thermal conductivity 2.3W / (m·K), parallel thermal conductivity 24W / (m·K), tensile strength 50MPa, flexural modulus 12GPa, which are significantly better than commercial carbon paper.
[0102] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A method for preparing micro-nanostructured carbon fiber paper for a gas diffusion layer, characterized in that: The following steps are involved: S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning; S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples; S3, mixing the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, a binder, a dispersant and water uniformly and then performing wet papermaking to obtain a micro-nanostructured carbon fiber base paper; S4, the micro-nano structure carbon fiber base paper is impregnated with resin, hot-pressed and cured, and heat-treated to obtain micro-nano structure carbon fiber paper for gas diffusion layer.
2. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 1, characterized in that: In step S1: The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.1-20):(500-3000); and / or The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; and / or The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or The stirring temperature is 30 to 90° C.; and / or The high-voltage electrospinning is one of single-needle, multi-needle and needle-free.
3. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 2, characterized in that: In step S1: The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.5-10):(800-2000); and / or The stirring temperature is 40-80°C.
4. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 1, characterized in that: In step S2: The pre-oxidation treatment is carried out in an air atmosphere at 180-300° C. for a treatment time of 0.5-5 h; and / or The boron-containing pre-oxidized nanofiber short filaments have a length of 0.5 to 12 cm and a diameter of 50 to 800 nm.
5. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 4, characterized in that: In step S2: In the pre-oxidation treatment, the treatment temperature is 200-280° C. and the treatment time is 1-4 hours; and / or The boron-containing pre-oxidized nanofiber short filaments have a length of 2 to 8 cm and a diameter of 100 to 600 nm.
6. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 1, characterized in that: In step S3: The weight ratio of the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (0.1-5):(0.1-5):(0.1-4):(0.05-2):100; and / or The chopped carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber and viscose-based carbon fiber; and / or The binder is selected from one or more of polyvinyl alcohol, epoxy resin and carboxymethyl cellulose; and / or The dispersant is selected from one of polyethylene oxide, polyacrylamide and sodium polyacrylate; and / or The thickness of the micro-nano structure carbon fiber base paper is 200-800 μm.
7. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 6, characterized in that: In step S3: The weight ratio of the boron-containing pre-oxidized nanofiber short filaments, chopped carbon fibers, binder, dispersant and water is (0.2-3):(0.2-3):(0.2-2.5):(0.1-1.5):100; and / or The thickness of the micro-nano structure carbon fiber base paper is 300-600 μm.
8. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 1, characterized in that: In step S4: The resin used for the impregnation resin is selected from one or more of phenolic resin, epoxy resin and furan resin; and / or During the hot pressing curing process, the hot pressing temperature is 80-300° C., the pressure is 0.5-20 MPa, and the hot pressing time is 1-30 min; and / or The heat treatment process is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or The thickness of the micro-nano structure carbon fiber paper for the gas diffusion layer is 100-400 μm.
9. The method for preparing micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 8, characterized in that: In step S4: During the hot pressing curing process, the hot pressing temperature is 100-240° C., the pressure is 1-10 MPa, and the hot pressing time is 2-15 min; and / or During the heat treatment, the heat treatment temperature is 800-2000° C. and the heat treatment time is 1-3 hours; and / or The thickness of the micro-nano structure carbon fiber paper for the gas diffusion layer is 140-280 μm.
10. A micro-nano structured carbon fiber paper for a gas diffusion layer prepared according to the method for preparing micro-nano structured carbon fiber paper for a gas diffusion layer according to any one of claims 1 to 9.
11. The micro-nanostructured carbon fiber paper for gas diffusion layer according to claim 10, characterized in that: The vertical air permeability of the micro-nanostructured carbon fiber paper for the gas diffusion layer is ≥2200 mL·mm / (cm 2 ·h·mmAq), vertical resistivity ≤55mΩ·cm, parallel resistivity ≤4.0mΩ·cm, tensile strength ≥50MPa, bending modulus ≥12GPa.
12. Use of the micro-nano structured carbon fiber paper for gas diffusion layer prepared by the method for preparing micro-nano structured carbon fiber paper for gas diffusion layer according to any one of claims 1 to 9 in the gas diffusion layer of a liquid flow battery.
Citation Information
Patent Citations
Preparation for carbon fiber paper used for gas diffusion layer of proton exchange membrane fuel cell
CN101591868A
Preparation method for boron-containing polyacrylonitrile protofilament and carbon fiber thereof and graphite fiber
CN106917156A
High-performance carbon paper for fuel cell and preparation method and application thereof
CN110512459A
Carbon fibre paper and its mfg. method
CN1598142A
Carbon fiber paper and porous carbon electrode substratefor fuel cell therefrom
CN1643213A
